Problems and Needs of Local Leaders towards Sustainable Agriculture in Organic Laying Hens Learning - Parichat Puramongkon,; Terdsak Puramongkon, (Journal of Educational Issues, 2024)
This research aims to study the problems and needs of local leaders towards sustainable agriculture in organic agriculture learning. Participants were 40 local leaders in the communities raising good-humored egg-laying hens. They are farmers who adhere to the sufficiency economy philosophy and intend to develop into an organic egg-laying hen production system in Khao Khitchakut District, Chanthaburi Province, Thailand. The tool used in the study was a questionnaire on farmers: production conditions, problems, and demand issues for good-humored egg-laying hens. The results found that they raised good-humored egg-laying hens and intended to develop into an organic system. However, they had less knowledge, experience, organic feed ingredients and understanding of organic feed production. The problem and demand in production remained at a low to moderate level. Even though the result indicated that the level of problems and needs are not high, knowledge development and the community's understanding of organic farming continue unceasingly since there is a demand for good-humored eggs. The government agencies should promote the transfer of production technology, production standard, inputs support, farm accounting, group publicity, online marketing, packaging suitable for long-distance transport and give suggestions for the group to have strength and sustainability in production.